Corilagin Ameliorates Con A-Induced Hepatic Injury by Restricting M1 Macrophage Polarization - Yan, Fenglian; Cheng, Dalei; Wang, Haiyan; Gao, Min; Zhang, Junfeng; Cheng, Hongyan; Wang, Changying; Zhang, Hui; Xiong, Huabao (Frontiers in Immunology, 2022)
Immune-mediated hepatic injury plays a key role in the initiation and pathogenesis of diverse liver diseases. However, treatment choice for immune-mediated hepatic injury remains limited. Corilagin, a natural ellagitannin extracted from various traditional Chinese medicines, has been demonstrated to exhibit multiple pharmacological activities, such as anti-inﬂammatory, anti-tumor, and hepatoprotective properties. The present study aimed to investigate the effects of corilagin on immune-mediated hepatic injury using a murine model of concanavalin A (Con A)-induced hepatitis, which is well-characterized to study acute immune-mediated hepatitis. Herein, mice were administered corilagin (25 mg/kg) intraperitoneally twice at 12 h intervals, and 1 h later, the mice were challenged with Con A (20 mg/kg body weight); serum and liver samples were collected after 12 h. The results showed that corilagin significantly increased the survival of mice and reduced serum alanine transaminase (ALT) and aspartate aminotransferase (AST) levels. In addition, corilagin markedly improved histopathological damage, hepatocyte apoptosis, and oxidative stress in the liver. The activation of M1 macrophages in the hepatic mononuclear cells was also significantly reduced compared with that in the control group. The expression of M1 macrophage-associated proinflammatory cytokines and genes, including interleukin (IL)-6, IL-12, and inducible nitric oxide synthase (iNOS), was also decreased after corilagin treatment. Finally, the results demonstrated that corilagin regulated macrophage polarization by modulating the mitogen-activated protein kinases (MAPK), nuclear factor (NF)-κB, and interferon regulatory factor (IRF) signaling pathways. Thus, the findings indicate that corilagin protects mice from Con A-induced immune-mediated hepatic injury by limiting M1 macrophage activation via the MAPK, NF-κB, and IRF signaling pathways, suggesting corilagin as a possible treatment choice for immune-mediated hepatic injury.